Dollar-Unit Sampling: A Practical Guide for Auditors. - Newman, Maurice S. (The Accounting Review, 1981)
Reviews the book "Dollar-Unit Sampling: A Practical Guide for Auditors," by Donald A. Leslie, Albert D. Teitlebaum and Rodney J. Anderson.